Teachers’ Union Demands and Prospects of Teachers in the Globalization Era - Soeganda Priyatna (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2003)
In Indonesian society, teacher has a unique position, beside as knowledge, perception, attitude, ehviour transferor also as a role model to the society. It is more than an evolutionary modernization; globalization has touched almost every aspects of life fantastically and jointly, shook every cultural foundations, roots and national defense. Together with family and society, teacher is an institution which tries to control them. In reality, teacher is expected to give his or her biggest effort compared to the other two. On the other hand, teacher burden felt harder from time to time in an artificial, economic oriented and marginalizing noble values society. Teacher is losing their prestige whereas teacher is also expected to be a multidimension person in this third millennium. Can the teacher fight for his or her right to live properly through a solid fight? Can the society accept the reality that as worker, teacher also has the right to build and become a member of a worker union? ILO Convention ratification four years ago showed that teacher is allowed to start his or her own worker union. Teacher’s Union must be a promoter to the development of teacher’s social economic status and professionalism and to push trade unionism to be a social movement.